Multi-Criteria and Multi-Dimensional Analysis in Decisions Decision Making with Preference Vector Methods (PVM) and Vector Measure Construction Methods (VMCM) - Nermend, Kesra (Vector Optimization, 2023)
XVI, 354 p. 120 illus.